Measuring the Effectiveness of Pertamina Pertamax TVC with Tukul Arwana as brand Ambassador by Using Epic Model - Baskoro, Dwi Grahantio; Hudrasyah, Herry (Journal of Business and Management, 2013)
Recently, coordinating minister of economics Indonesia, Hatta Rajasa found out that middle-up class consumes 70% quota of BBM PSO (public service obligation). According to the data, economist Dradjad Wibowo made a calculation of it. Based on data in 2011, Indonesia subsidized for about 115.6 Trillion from total 165.2 Trillion for middle-up class consumers. Head of BPH Migas Andy Norsaman Someng also mentioned that government already increased the quota of BBM PSO from 44 million KL in 2012 to 46 million KL in 2013. He explained that to reduce scarcity of BBM PSO in several SPBU in Indonesia, increasing quota is the best solution. Based on the facts and background, Pertamina committed to increase consumer’s attention of Pertamax. Promotion can be done in several ways, one of it is advertising. Pertamina already launch their ad before, but almost the theme is same. It can be seen that Pertamina is too selling their product rather than getting awareness through the consumers. Afterwards, Pertamina choose Tukul Arwana as the new brand ambassador of Pertamax. He presents in the new ad that contained new theme, which is to gain more emotional side of consumers. In the same time, this breakthrough ad creates questions of the effectiveness with the original Pertamina’s goals to increase consumer’s attention of Pertamax.  The main objective of the research is to measure the effectiveness of the new Pertamax ad with Tukul Arwana as brand ambassador by using EPIC model, which developed by AC Nielsen. EPIC is consists of empathy, persuasion, impact and communication. Research is conducted with qualitative and quantitative research. For quantitative research, questionnaire is distributed to 278 respondents from Bandung who categorize as Y generation. Y generation is chosen because Gen Y is known as incredibly sophisticated, technology wise, immune to most traditional marketing and sales pitches. All of the analysis is processed using Microsoft Excel and SPSS. Microsoft Excel is used to analyze using Descriptive method, while SPSS is used to analyze the pre-test and factor analysis. Pre-test is conducted to the first 30 respondents with all results is valid. It is shown from all items’ Pearson correlation is above 0.3. Descriptive analysis represents score of each dimension. From the result, communication dimension get the highest score with 72.13%, while the lowest is persuasion with 65.15%. This means the most affecting factor from Pertamax ad with Tukul as brand ambassador is Communication. Keywords: Advertising, Effectiveness, Pertamax, Tukul Arwana, EPIC model-------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.